Relationship Between Language Learning Strategy Use and Reading Comprehension Among Iranian Undergraduate EFL Learners - Zare, Pezhman Zare (2011)
The present study focuses on determining the language learning strategy use of undergraduate Iranian language learners in learning English as a foreign language. It also aims to investigate the relationship between language learning strategy use and reading comprehension. Moreover, the study explores the category of strategies which is more predictive of reading comprehension success and also determines how the use of learning strategies varies according to gender. One hundred and forty eight students were selected through cluster random sampling to participate in the study as a sample. The Strategy Inventory for Language Learning (SILL) (Oxford, 1990) was used to elicit information on the use of language learning strategies and a reading comprehension test was used to assess the participants’ performance on reading comprehension. The collected data were analyzed through descriptive statistics to determine the frequency and type of learning strategies employed by Iranian EFL learners. Pearson coefficient correlation was used to find out the association between language learning strategy use and reading comprehension success. Multiple regression analysis was run to investigate the category of strategies which was more predictive of reading comprehension achievement, and Chi-square test was employed to determine how the use of learningstrategies varied according to gender. The findings of the study revealed that Iranian undergraduate EFL learners can be categorized as medium strategy users with the overall mean score of 3.35. Moreover, the mean scores of categories of learning strategies ranged from 3.11 to 3.64 and also 47% of the students reported to employ language learning strategies with medium frequency. The results also demonstrated that the overall use of language learning strategies had a strong positive correlation with reading comprehension achievement. Furthermore, the results of multiple regression analysis depicted that the category of metacognitive strategies was the best predictor of reading comprehension achievement. The findings also showed that the overall use of language learning strategies significantly varied according to gender. Female EFL learners significantly prevailed over males in the use of learning strategies.